A Bile Salt Hydrolase of Brucella abortus Contributes to the Establishment of a Successful Infection through the Oral Route in Mice - Delpino, M. Victoria (American Society for Microbiology, 2007)
Choloylglycine hydrolase (CGH), a bile salt hydrolase, has been annotated in all the available genomes of Brucella species. We obtained the Brucella CGH in recombinant form and demonstrated in vitro its capacity to cleave glycocholate into glycine and cholate. Brucella abortus 2308 (wild type) and its isogenic Δcgh deletion mutant exhibited similar growth rates in tryptic soy broth in the absence of bile. In contrast, the growth of the Δcgh mutant was notably impaired by both 5% and 10% bile. The bile resistance of the complemented mutant was similar to that of the wild-type strain. In mice infected through the intragastric or the intraperitoneal route, splenic infection was significantly lower at 10 and 20 days postinfection in animals infected with the Δcgh mutant than in those infected with the wild-type strain. For both routes, no differences in spleen CFU were found between animals infected with the wild-type strain and those infected with the complemented mutant. Mice immunized intragastrically with recombinant CGH mixed with cholera toxin (CGH+CT) developed a specific mucosal humoral (immunoglobulin G [IgG] and IgA) and cellular (interleukin-2) immune responses. Fifteen days after challenge by the same route with live B. abortus 2308 cells, splenic CFU counts were 10-fold lower in mice immunized with CGH+CT than in mice immunized with CT or phosphate-buffered saline. This study shows that CGH confers on Brucella the ability to resist the antimicrobial action of bile salts. The results also suggest that CGH may contribute to the ability of Brucella to infect the host through the oral route.